Comparative constitutionalism and good governance in the Commonwealth an Eastern and Southern African perspective - Hatchard, John (Cambridge University Press, 2004)
The central role that good, effective and capable governance plays in the economic and social development of a country is now widely recognised. Using the Commonwealth countries of eastern and southern Africa, this book analyses some of the key constitutional issues in the process of developing, strengthening and consolidating the capacity of states to ensure the good governance of their peoples. Utilising comparative material, the book seeks to draw lessons, both positive and negative, about the problems of constitutionalism in the region and, in doing so, critically addresses the legal issues involved in seeking to make constitutions 'work' in practice
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Commonwealth; Politik; Verfassungsrecht; Constitutional law / Africa, East; Constitutional law / Africa, Southern; Constitutional law / Commonwealth countries; Rechtsvergleich; Politisches System; Africa, East / Politics and government; Africa, Southern / Politics and government; Commonwealth countries / Politics and government; Afrika